ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP NIAT MEREKOMENDASIKAN DAN MENGULANGI KUNJUNGAN YANG DI MEDIASI OLEH KEPUASAN PENGUNJUNG (PEMECAHAN MASALAH FENOMENA BISNIS OWABONG) - Ridho Bahthiar; Pramono Hari Adi (Faculty of Economics and Business Universitas Jenderal Soedirman, 2011)
This study is an applicative study, entitled Ã¢â‚¬Å“Analysis of The Influence of Service Quality To Recommend and Revisit Intentions Are Mediated By Visitor Satisfaction (Problem Solving of Owabong Business Phenomenon)Ã¢â‚¬Â. Since the waterpark phenomenon has been growing rapidly over the past several years, visitor loyalty has emerged as a strategic imperative for this bussiness and make the waterpark manager must compete to maintain the loyalty of their visitors. The purpose of this study was to solve waterpark bussiness phenomenon, especially in Owabong waterpark. Population and subject in this study were visitors of Owabong waterpark in Purbalingga. This study empirically investigated five dimensions of service quality (facility, staff emphaty, responsiveness, assurance, and benefits), visitor satisfaction and two dimensions of visitor loyalty (recommend and revisit intentions) from waterpark. Data were collected from 110 visitor. Accidental sample technique was used for the data analysis. Through a questionnaire survey and SEM (Structural Equation Modelling) analysis, the results of this study indicated that three dimensions of service quality (facility, staff emphaty, and assurance) hasnÃ¢â‚¬â„¢t influence on visitor satisfaction. Meanwhile, two dimensions of waterpark service quality (responsiveness and benefits) has influence on visitor satisfaction and then generates two dimensions of visitor loyalty (recommend and revisit intention). Conclusions indicate that waterpark management should optimalize their facility presentation and their staff participation, and improve promotion strategies for introducting their value to visitor.